Incidence rate and burden of illness at the Pyeongchang 2018 Paralympic Winter Games. Issue 17 (13th September 2019) - Derman, Wayne; Runciman, Phoebe; Jordaan, Esme; Schwellnus, Martin; Blauwet, Cheri; Webborn, Nick; Lexell, Jan; van de Vliet, Peter; Kissick, James; Stomphorst, Jaap; Lee, Young-Hee; Kim, Keun-Suh
Abstract : Objective: To describe the incidence rate (IR) and illness burden (IB) at the Pyeongchang 2018 Paralympic Winter Games. Methods: A total of 567 athletes from 49 countries were monitored for 12 days over the Pyeongchang 2018 Games (6804 athlete days). Illness data were obtained daily from teams with (41 teams, 557 athletes) and teams without (8 teams, 10 athletes) their own medical support, through electronic data capturing systems. Results: There were 87 illnesses reported, with an illness IR of 12.8 illnesses per 1000 athlete days (95% CI 10.2 to 16.0) and IB of 6.8 days lost per 1000 athlete days (95% CI 3.4 to 13.5). The highest IR was reported for Para snowboard (IR of 19.7 [95% CI 12.0 to 32.2]). Illnesses in the respiratory system (IR of 4.1 [95% CI 2.9 to 5.9]; IB of 1.4 [95% CI 0.6 to 3.0]), skin and subcutaneous system (IR of 2.5 [95% CI 1.5 to 4.1]; IB of 0.6 [95% CI 0.1 to 2.9]), and eye and ocular adnexa (IR of 1.6 [95% CI 0.9 to 3.1]; IB of 0.5 [95% CI 0.1 to 3.3]) were the most common. Conclusion: This is the first study to report both the IR and IB in this setting. There was a high IR of illness in the new sport of Para snowboard. The respiratory system had both the highest IR and IB.